2003
DOI: 10.1002/jbm.a.20082
|View full text |Cite
|
Sign up to set email alerts
|

RGD‐containing peptide GCRGYGRGDSPG reduces enhancement of osteoblast differentiation by poly(L‐lysine)‐graft‐poly(ethylene glycol)‐coated titanium surfaces

Abstract: Osteoblasts exhibit a more differentiated morphology on surfaces with rough microtopographies. Surface effects are often mediated through integrins that bind the RGD motif in cell attachment proteins. Here, we tested the hypothesis that modulating access to RGD binding sites can modify the response of osteoblasts to surface microtopography. MG63 immature osteoblast-like cells were cultured on smooth (Ti sputter-coated Si wafers) and rough (grit blasted/acid etched) Ti surfaces that were modified with adsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 80 publications
7
145
1
3
Order By: Relevance
“…Related studies in our lab using PT and SLA substrates coated with polyethylene glycol and functionalized with an RGD-containing peptide demonstrated suggested that greater numbers of attachment sites might actually result in a less differentiated cell [18]. The behavior of MG63 cells on coated SLA could be restored to the behavior of these cells on PT and even tissue culture plastic simply by increasing the number of RGD peptides on the surface.…”
Section: Role Of Integrinsmentioning
confidence: 79%
“…Related studies in our lab using PT and SLA substrates coated with polyethylene glycol and functionalized with an RGD-containing peptide demonstrated suggested that greater numbers of attachment sites might actually result in a less differentiated cell [18]. The behavior of MG63 cells on coated SLA could be restored to the behavior of these cells on PT and even tissue culture plastic simply by increasing the number of RGD peptides on the surface.…”
Section: Role Of Integrinsmentioning
confidence: 79%
“…The uncertainties introduced by working with natural protein layers has driven the development and synthesis of materials which provide full control over the ligandreceptor interactions (Hubbell, 1999), not only for optimizing cell culture labware but also for the development of smart materials in regenerative medicine. To this end, RGD grafted poly-L-lysine-graftpoly(ethylene glycol) (PLL-g-PEG) copolymers offer an elegant solution to block non-specific protein adsorption from serum through their PEG compartment, while introducing biofunctionality via PEG chains grafted with a peptide that contains the cell adhesion sequence RGD (VandeVondele et al, 2003, for a schematic depiction see Fig. 1).…”
Section: Rgd-peptide Restricted Interactions and Cartilage Formationmentioning
confidence: 99%
“…The biology of chondrocytes is highly influenced by interactions with specific extracellular matrix (ECM) molecules (Scully et al, 2001;van der Kraan et al, 2002). Thus, targeted modification of cell culture substrates with biological motives has the potential to improve HAC expansion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the RGD motif, as discussed before, is one of the most studied protein sequence capable of promoting cell adhesion and thereby initiating intracellular signalling cascades through multiple integrins including  v  3 and  5  1 (Ruoslahti, 1996). This motif is usually covalently attached to titanium using silanization (Bagno et al, 2007) or functionalized using polymer chemistry (Tosatti et al, 2004), and has been reported to increase osteoblast attachment and proliferation (Schuler et al, 2006). While several in vivo studies (Elmengaard et al, 2005;Kroese-Deutman et al, 2005) demonstrated better osseointegration results, others did not find any significant enhancement for the RGD functionalization (Petrie et al, 2008;Schliephake et al, 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%